Effects of nanoscale zero-valent iron loaded biochar on the fate of phenanthrene in soil-radish (Raphanus sativus L. var.radculus pers) system - Lianzhou Shen; Yue Cai; Juan Gao (Eco-Environment & Health)
Nanoscale zero-valent iron loaded on biochar (nZVI@BC) has been proven to be effective in activating persulfate to remediate soil organic pollutants. However, studies on subsequent plant growth and microbial community changes in remediated soil remain limited. In this study, nZVI@BC, nZVI, and nanoscale biochar (nBC) were ball-mill produced and applied as amendments in pot experiments with PAH-contaminated soil to investigate their impacts on soil-crop (radish, Raphanus sativus L.) systems, and the widely distributed phenanthrene (Phe) was selected as model pollutant. The results indicate that nZVI@BC could induce more (75%) Phe accumulation in radish compared to the control treatment, but did not result in significant differences in plant biomass or enzyme activity. In Phe non-contaminated treatments, the Fe content of radish shoots increased from 86.87 ± 5.61 mg/kg DW without material application to 125.20 ± 11.93 mg/kg DW with nZVI@BC, while no significant differences were observed in roots. nZVI@BC and nBC increased the non-desorbed fraction of PAHs with low bio-availability by 13.6% and 10.2%, respectively, after 45 days compared to the control treatment. Illumina MiSeq sequencing revealed that nZVI@BC did not adversely affect the richness and diversity of soil microbial communities. Instead, it promoted the enrichment of bacteria related to the degradation of organic pollutants, such as Lysobacter and Spingomonas. The findings suggest that nZVI@BC after chemical oxidation remediation might be harmful to subsequent plants and ecosystems but much better than nZVI alone. The amount of nZVI@BC should be accurately calculated before chemical oxidation remediation.